Front Cover: Reprogramming Stem Cells in Regenerative Medicine (Smart Medicine 1/2022). Issue 1 (30th December 2022) - Mao, Jiayi; Saiding, Qimanguli; Qian, Shutong; Liu, Zhimo; Zhao, Binfan; Zhao, Qiuyu; Lu, Bolun; Mao, Xiyuan; Zhang, Liucheng; Zhang, Yuguang; Sun, Xiaoming; Cui, Wenguo
Abstract : Induced pluripotent stem cells (iPSC) that are generated from adult somatic cells are induced to express genes that make them pluripotent through reprogramming techniques, which may open up new possibilities for regenerative medicine to treat diseases in the future. Biotechnological, chemical, and physical modulation techniques are different reprogramming cell technologies to obtain iPSC and present their respective strengths in iPSC reprogramming‐based regenerative therapies, such as hair follicle defects, myocardial infarction, neurological disorders, liver diseases, and spinal cord injuries.